A direct contact cooler design for simultaneously recovering latent heat and capturing SOx and NOx from pressurized flue gas. (15th February 2022) - Verma, Piyush; Yang, Zhiwei; Axelbaum, Richard L.
Highlights: Novel design and optimization of a DCC for SOx -NOx scrubbing and latent heat recovery. Multi-injection optimized DCC has faster condensation compared to conventional DCC. NOx and SOx scrubbing enhanced by 9 and 3.5 percentage points respectively. NOx scrubbing enhancement through increased residence time and kinetic constant. SOx scrubbing enhancement through increased liquid phase interaction. Abstract: Integrated SOx and NOx removal technology using a direct contact cooler is a promising alternative for cleaning coal combustion flue gas, especially for pressurized combustion systems. Past investigations of integrated SOx and NOx removal have been limited to low-temperature processes, where the flue gas has been cooled upstream of the removal unit, and the moisture in the flue gas has been condensed out. This work presents a novel design that recovers the flue gas heat while simultaneously removing SOx and NOx in a single reactive-absorption column – direct contact cooler. A validated model was used to evaluate different direct contact cooler designs. Modeling results suggested that a counter-current column with a single water inlet can scrub 83% of the NOx and 96.5% of the SOx in 115 s, while an optimized design with multiple water inlets enhances the scrubbing of NOx by 9 percentage points and SOx by 3.5 percentage points, due to a 34% increase in residence time. It is also observed that the liquid-phase reaction between absorbed SOx and NOx plays a significant role in the removal of SO2 from the flue gas for high-temperature scrubbing compared with low-temperature scrubbing. The design reinforces the potential of high-temperature SOx -NOx removal and heat recovery and suggests a means of reducing capital costs for such columns.